Beyond Bias and Culture: Exploring the Role of Sustainable Procurement Orientation in Vendor Selection and Procurement Performance in the Construction Industry - Gemmi Puspa Wijayanti Irianto; Agus Purnomo; Melia Eka Setiani (Dinasti International Journal of Education Management and Social Science, 2025)
This study aims to examine the influence of Organisational Culture, Perceived Risk, Status Quo Bias, and Sustainable Procurement Orientation on Vendor Selection and Procurement Performance in the construction industry, and to assess the mediating role of Vendor Selection. A quantitative approach was applied using survey data from 112 employees involved in procurement activities at a construction company in Indonesia, and the data were analysed using Partial Least Squares–Structural Equation Modelling. All constructs met the criteria for reliability and both convergent and discriminant validity. Organizational Culture emerged as the strongest predictor of Vendor Selection and Procurement Performance, followed by Sustainable Procurement Orientation. Contrary to theoretical expectations, Perceived Risk and Status Quo Bias showed positive effects on Vendor Selection, indicating the strategic importance of caution and stability in high-risk construction environments. Vendor Selection significantly mediated all examined relationships. These findings enhance the understanding of behavioral dynamics in supply chains and sustainable procurement by demonstrating how psychological, cultural, and sustainability-oriented factors collectively shape vendor decision-making and influence procurement outcomes.